FORMULASI DAN EVALUASI SEDIAAN LIPSTIK MENGGUNAKAN PEWARNA ALAMI DARI EKSTRAK ETANOL BUAH BIT (Beta vulgaris L.) - Elsan Fitri Artanti; Astriani Natalia Br. Ginting; Vera Estefania Kaban (Jurnal Buana Farma, 2026)
Lip color is a cosmetic preparation used to color the lips with an artistic touch, thereby enhancing facial aesthetics in makeup application. Long-term use of lipstick containing synthetic dyes such as Rhodamine B may cause cancer and impair liver and kidney function. One plant that can serve as a natural coloring source is beetroot (Beta vulgaris L.), which contains betalain pigments classified as antioxidants. This study aimed to determine whether ethanol extract of beetroot can be formulated into a lipstick preparation as a natural colorant. This experimental research was conducted through several stages, including plant identification, collection, simplicia preparation, characterization, extraction using 70% ethanol, thin-layer chromatography (TLC) analysis, formulation, and evaluation of product quality. The evaluation included organoleptic testing, homogeneity, pH, melting point, hardness, spreadability, irritation test, hedonic test, and stability test. The TLC results showed that ethanol extract of beetroot was positive for flavonoids, alkaloids, tannins, saponins, and steroids. Lipstick formulations containing 15%, 20%, and 25% ethanol extract of beetroot were semi-solid with brown and dark brown colors, homogeneous, and had pH values within the Indonesian National Standard (SNI) range of 4.5–7.0. The melting points ranged from 50–63°C. The spreadability was glossy and evenly distributed, the hardness met SNI requirements, and the formulations did not cause irritation. Formula F3 was most preferred by the panelists, and all formulations remained stable during storage at 4°C and 40°C. In conclusion, the ethanol extract of beetroot can be formulated into a lipstick preparation as a natural colorant and demonstrates good physical quality.